Does Culture Matter in Fraud Prevention Behavior? National Culture Based Study of Indonesian Bankers - Irawanto, Dodi Wirawan (Jurnal Keuangan dan Perbankan, 2018)
The rapid global movement questions on how a person had a worldview and how his behavior was influenced by its culture. International business meant that culture frequently used by social science researchers in the national cultural dimensions and that related to the economic growth of the financial aspect. Fraud prevention predicted to have a relation to a national culture that was on how the organization created ethical behavior through good corporate governance. This survey explored some important concepts regarding the national culture dimensions that tend to strengthen the fraud prevention actions on Indonesian State Owned Enterprises (SOEs) Bank in East Java as well as to develop an anti-fraud strategy that can be used as one of the efforts in fraud prevention. The findings suggest that national culture played an important role in creating fraud prevention behavior with long-term orientation as the key aspects to be considered in creating a successful organization strategy to combat fraud. JEL Classification: D23, F52, K42DOI: https://doi.org/10.26905/jkdp.v22i3.2139